Nanomaterials - Acetylcholinesterase Enzyme Matrices for Organophosphorus Pesticides Electrochemical Sensors: A Review - Shen-Ming Chen; Arun Prakash Periasamy; Yogeswaran Umasankar (Sensors, 2009)
Acetylcholinesterase (AChE) is an important cholinesterase enzyme present in the synaptic clefts of living organisms. It maintains the levels of the neurotransmitter acetylcholine by catalyzing the hydrolysis reaction of acetylcholine to thiocholine. This catalytic activity of AChE is drastically inhibited by trace amounts of organophosphorus (OP) pesticides present in the environment. As a result, effective monitoring of OP pesticides in the environment is very desirable and has been done successfully in recent years with the use of nanomaterial-based AChE sensors. In such sensors, the enzyme AChE has been immobilized onto nanomaterials like multiwalled carbon nanotubes, gold nanoparticles, zirconia nanoparticles, cadmium sulphide nano particles or quantum dots. These nanomaterial matrices promote significant enhancements of OP pesticide determinations, with the thiocholine oxidation occurring at much lower oxidation potentials. Moreover, nanomaterial-based AChE sensors with rapid response, increased operational and long storage stability are extremely well suited for OP pesticide determination over a wide concentration range. In this review, the unique advantages of using nanomaterials as AChE immobilization matrices are discussed. Further, detection limits, sensitivities and correlation coefficients obtained using various electroanalytical techniques have also been compared with chromatographic techniques.